A comprehensive review on nanobiotechnology for bioremediation of heavy metals from wastewater. (2nd January 2022) - Malik, Sumira; Kishore, Shristi; Shah, Maulin P.; Kumar, Shradha A.
Abstract: Removal of contaminants from wastewater is a big concern for the scientific community. Heavy metals are one of the major contaminants present in wastewater. Heavy metals such as Cd 2+, Pb 2+, Mn 2+, and so forth, are highly toxic and pose a serious threat to the environment due to their nonbiodegradable nature. With the advent of nanobiotechnology, heavy metal contaminants can be mitigated with the help of nanomaterials produced by eco‐friendly methods. Specially designed bionanomaterials often exhibit properties such as increased shelf life, self‐healing nature, adaptability in different environments, and cost‐effectiveness, thus showing advantages over nanomaterials produced by physicochemical methods. Due to their high specificity and adsorption capacity, bionanomaterials can remove heavy metals present even in a very low concentration in wastewater. The use of bionanotechnology in their remediation paves a way for environmental sustainability and helps in cost reduction. This paper intends to discuss the nanobiotechnological approach for the remediation of heavy metals from wastewater. Furthermore, the paper also reviews some important nanomaterials and their potential applications in the depollution of heavy‐metal contaminated wastewater.